Appraisal of Heavy Metals in the Fish Sarotherodon galilaeus and Sarotherodon melanotheron from Alaro Stream in Ibadan, Nigeria (2017)
An appraisal was carried out on the heavy metals in the fish Sarotherodon melanotheron and Sarotherodon galilaeus from Alaro Stream in Ibadan. The study was carried out because fish is a major source of affordable protein for the ever growing global human population. The concentration of heavy metals in the aquatic ecosystem as a result of human activities at any given time portend a health risk for consumers of fish and its products. A total of fifty fish comprising S. melanotheron (25) and S. galileaus (25) were collected from the study area. Dissected and pulverized fish organ samples were acid- digested in Teflon tubes for analyses using the Inductively Coupled Plasma Mass Spectrometer (ICP-MS). The mean Ni in the liver, gut and fins of both fish exceeded the World Health Organization (WHO) limit guideline (0.07ppm). All the mean Se concentration in the organs of the two fish were all above the WHO limit guideline of 0.04ppm. With the exception of the muscle (0.01ppm) in S. galilaeus, all the other mean V concentration in the organs of the two fish were higher than the limit guideline of 0.02ppm while there is no current value for Mn and Co. The study shows that organs of S. galilaeus and S. melanotheron had V, Ni and Se above the World Health Organization’s limit guidelines thereby making the fish unfit for human consumption as long as the effluents discharged into the stream remain untreated. Continuous biomonitoring of the aquatic ecosystem for heavy metal pollution is recommended.